A study on the effect of game base balance training and gender difference on attention and memory by eye tracking method - Ting, Tan Wei (2021)
Game base balance training was shown to be effective in improving cognition as more cognitive resources can be allocated to deal with cognitive tasks due to improve balance ability. In addition, there is gender difference in cognitive performances. Thus, in this study, game base balance training was conducted to examine its effect on improving visual attention and working memory among healthy male and female university students. The aim of this study is to investigate the effect of balance training and gender difference on visual attention and working memory performances. This study is an interventional study with randomized controlled trial. The target population is students from University Sains Malaysia, Kubang Kerian who fulfil the subject criteria and pass the screening tests. There were three screening tests which were the Ishihara Color Blindness Test, Physical Activity Readiness Questionnaire (PAR-Q) and Balance Performance Assessment from Fitness Balance Board (FIBOD). The sample size is 48 participants. As this study is also interested in gender differences in cognition, an equal number of male and female was recruited and randomly assigned to either the experimental or control group. The intervention was carried out using FIBOD with Space Shooter. Pre and post-tests included Balance Error Scoring System (BESS) to measure balance ability; Visual Search Task to measure attention; and Mnemonic Similarity Task to measure memory. The two cognitive assessments were conducted with eye tracking. The control group only underwent the pre and post assessments and was refrained from doing other balance training. Other than the pre and post assessments, the experimental group also underwent the intervention for one month, with three 15-minutes sessions in a week. To analyse the data, SMI BeGaze and Statistical Package for Social Sciences were used. The statistical test used to analyse the collected data was Repeated Measures ANOVA. There were two outcome measures in each cognitive tests, response time and accuracy. For visual attention, there was a significant interaction effect in response time between the two groups from pre to post assessment, F (1, 46) = 16.80, p < .014, ηp2 = .268. As for the accuracy in visual attention, there was a significant interaction effect, F (1, 46) = 20.47, p < .000, ηp2 = .308. To compare visual attention between gender, there were no significant difference in response time F (1, 46) = 1.64, p = .213, ηp2 = .069 as well as in accuracy F (1, 46) = 0.11, p = .745, ηp2 = .005 between gender from pre to post assessments. For working memory, there is no significant interaction effect in response time F (1, 46) = 2.01, p = .163, ηp2 = .042 and accuracy F (1, 46) = 0.06, p = .805, ηp2 = .001 between the two groups from pre to post assessments. To compare working memory between gender, there were no significant difference in response time F (1, 46) = 0.81, p = .378, ηp2 = .035 as well as in accuracy F (1, 46) = 2.79, p = .109, ηp2 = .112 between gender from pre to post assessments. Game base balance training used in this study was able to improve cognitive performances among healthy university students. The experimental group showed improved performance in visual attention and working memory between pre and post assessments. Yet, the experimental group only performed better than the control group in the visual attention task but in not the working memory task. No significant gender differences were found in both visual attention and working memory performances after the intervention.